Pengaruh Kualitas Komite Audit dan Ukuran Kantor Akuntan Publik terhadap Manajemen Laba - Nazila Alfiyasahra; Auliffi Ermian Challen (Jurnal Akuntansi Indonesia, 2020)
This study aims to determine the effect of the quality of the audit committee and the size of the public accounting firm on earnings management. The audit committee uses the proxy size of the audit committee, the number of audit committee meetings, the independent audit committee and the expertise of the audit committee. This study uses secondary data, namely companies in the category of basic industrial and chemical manufacturing sectors listed on the Indonesia Stock Exchange (IDX). The sample used 16 companies with the period 2015-2017 through a purposive sampling method. The analytical method used is multiple regression. Based on the results of the study concluded that the independent audit committee has a positive effect on earnings management, but the size of the audit committee, the number of audit committee meetings, the expertise of the audit committee, and the size of the public accounting firm have no influence on earnings management.